Analysis and exact solutions for reaction-diffusion predator-prey system with prey-taxis by ?6 method - Naeem, Rishi; Iqbal, Muhammad Sajid; Ali, Ali Hasan; İnç, Mustafa (Vilnius Univ Press, 2025)
This article analyses the biomathematical model that describes the reaction-diffusion predator-prey system with prey-taxis. The analysis includes addressing the question of whether the solution exists and is unique. The next goal is to obtain the exact solutions. The phi 6 method has been utilized for this purpose. The simulations of the obtained solutions are also incorporated, providing a broader understanding of the solutions.
Keywords: nonlinear fractional-order partial differential equations; exact solutions; phi 6 method